Eye on the Future: Virtual Reality Surgical Simulator - Srishti Khullar; Sanjay Kumar Mishra; Amrita Joshi; Alok Sati; Pradeep Kumar; Deepesh Unni (Delhi Journal of Ophthalmology)
The virtual reality (VR) surgical simulator marks the beginning of an era of technology-based teaching which will help the trainees learn new perspectives on surgical anatomy and repeatedly practice intricate microsurgical steps to their way to perfection. These simulators aid in reducing the initial learning curve for ophthalmology training, improve technical skill acquisition, decrease technical errors in basic surgical skills, and provide a more structured method of evaluation of training. This review will focus on the types, applications, utility, and benefits of adding VR simulation to the residency training curriculum.